Is function in instrumental activities of daily living a useful feature in predicting Alzheimer's disease dementia in subjective cognitive decline?. (9th November 2018) - Roehr, Susanne; Riedel‐Heller, Steffi G.; Kaduszkiewicz, Hanna; Wagner, Michael; Fuchs, Angela; van der Leeden, Carolin; Wiese, Birgitt; Werle, Jochen; Bickel, Horst; König, Hans‐Helmut; Wolfsgruber, Steffen; Pentzek, Michael; et al.
Abstract : Objective: Subjective cognitive decline (SCD), the earliest symptom in preclinical Alzheimer's disease (AD), is insufficient to identify individuals at risk for AD dementia. Therefore, we aimed to investigate whether function in instrumental activities of daily living (IADL) contributes to identification. Methods: We analysed data of cognitively unimpaired participants of the prospective German Study on Ageing, Cognition, and Dementia in Primary Care Patients (AgeCoDe) and its extension, the Study on Needs, Health Service Use, Costs and Health‐related Quality of Life in a Large Sample of Oldest‐old Primary Care Patients (AgeQualiDe), collected over 10.5 years. Development of AD dementia was quantified as incidence rates (IRs) per 1000 person‐years. Cox regression was used to assess the association of SCD and IADL function in regard to incident AD dementia. Results: Of 1467 included individuals, 792 (54.0%) reported SCD at baseline. Impaired IADL were present in 50 (3.4%) individuals. IR for AD dementia was highest in individuals with SCD and impaired IADL (49.7; 95% CI, 24.8‐99.3). Unadjusted and adjusted Cox analyses revealed an increased AD dementia risk for individuals with SCD and impaired IADL (uHR = 6.1; 95% CI, 2.9‐13.0; P < 0.001; aHR = 2.5; 95% CI, 1.1‐5.7; P < 0.05). Conclusions: Consistent with the SCD concept, IADL function was largely well preserved in the majority of individuals with SCD. However, if difficulties in IADL were present, risk for AD dementia was increased. Therefore, screening for IADL impairment could serve as an economically viable indicator to assess AD dementia risk above and beyond SCD.